Additivity‐based design of the strongest possible turkey ovomucoid third domain inhibitors for porcine pancreatic elastase (PPE) and Streptomyces griseus protease B (SGPB). Issue 18 (23rd July 2013) - Qasim, Mohammad A.; Wang, Lixia; Qasim, Sabiha; Lu, Stephen; Lu, Wuyuan; Wynn, Richard; Yi, Zheng-Ping; Laskowski, Michael
Abstract : We describe here successful designs of strong inhibitors for porcine pancreatic elastase (PPE) and Streptomyces griseus protease B (SGPB). For each enzyme two inhibitor variants were designed. In one, the reactive site residue (position 18) was retained and the best residues were substituted at contact positions 13, 14, and 15. In the other variant the best residues were substituted at all contact positions except the reactive site where a Gly was substituted. The four designed variants were: for PPE, T 13 E 14 Y 15 ‐OMTKY3 and T 13 E 14 Y 15 G 18 M 21 P 32 V 36 ‐OMTKY3, and for SGPB, S 13 D 14 Y 15 ‐OMTKY3 and S 13 D 14 Y 15 G 18 I 19 K 21 ‐OMTKY3. The free energies of association (Δ G 0 ) of expressed variants have been measured with the proteases for which they were designed as well as with five other serine proteases and the results are discussed. Abstract : Successful application of sequence to reactivity algorithm for Kazal inhibitors. Additivity‐based design of strong inhibitors for two serine proteases. Amino acid changes at inhibitor contact positions are highly additive.